The Principle of Moderatism in The Formation of Fatwa of The Indonesian Ulema Council Number 83 of 2023 - Ramdlany, Ahmad Agus; Musadad, Ahmad (RechtIdee, 2024)
This study analyses the principle of moderatism (wasathiyyah) in the formation of fatwas of the Indonesian Ulema Council (MUI), particularly Fatwa No. 83 of 2023 on the Law of Supporting the Palestinian Struggle. The principle of wasathiyyah, which is at the core of Islamic jurisprudence, encourages a balanced and moderate approach in legal and ethical matters. This research uses a qualitative method, with data collected through document analysis of fatwa texts, related scholarly works, and other relevant literature. The analysis aims to reveal how the wasathiyyah principle is reflected in the formation of the fatwa and its implications for Indonesian Muslim society. The results show that MUI Fatwa No. 83 of 2023 integrates the principle of moderatism in several key aspects. Firstly, it emphasises the importance of supporting the Palestinian cause as a humanitarian and ethical obligation, in accordance with the principles of justice and solidarity in Islam. Secondly, it balances such support with an invitation to use peaceful and legitimate means, rejecting extremism and violence. This reflects a deep understanding of wasathiyyah, which encourages proactive yet peaceful engagement in international solidarity. In addition, the fatwa highlights the role of Indonesian Muslims in fighting for Palestinian rights through diplomatic, economic, and educational efforts. This broadens the scope of support beyond mere political activism, encouraging a multifaceted approach that integrates ethical, legal and humanitarian dimensions.